Evaluation in ELT - Matějková, Lucie (Univerzita Pardubice, 2008)
This thesis is dealing with the evaluation in ELT and the attention is focused on the individual progress norm. After mentioning the main characteristics of the individual as well as social progress norm, the individual progress norm and its benefits and limitations are further discussed. Furthermore, a qualitative research is described. The aim of the research is to find out whether and to what extent do the teachers of English use the individual progress norm when they evaluate.
Evaluace ve výuce anglického jazyka
Keywords: ELT; Evaluation; individual progress norm; social progress norm; individualization; Výuka anglického jazyka; evaluace; individuální vztahová norma; sociální vztahová norma; individualizace